Redemption bay eaudiobook Haven point series, book 2. - Thayne, RaeAnne (Haven Point, 2015)
New York Times bestselling author RaeAnne Thayne brings you back to Haven Point-a place made for second chances. McKenzie Shaw would do anything for her hometown of Haven Point. It may be small, but it's never let her down.unlike gorgeous, infuriating Ben Kilpatrick. He was her childhood hero until he closed his family's factory, leaving the town's economy in shambles. Now his tech firm is considering opening a local facility. For Haven Point's sake, McKenzie has to grit her teeth and play nice. What could a town filled with painful memories ever offer Ben? Yet seeing the town through the eyes of McKenzie-its fiery young mayor-he suddenly has his answer. If only he can resolve the animosity crackling between them, Ben may have found the place where he can build ties and find healing.a place where love arrives when it's least expected.